Rightful resistance: how do digital platforms achieve policy change? - Wen, Y (Elsevier, 2023)
Many digital platforms have disrupted not only the market but also public policies. Platform companies have been shown to employ various political strategies such as lobbying and petitions to change restrictive policies. However, previous literature has failed to consider the unique nature of digital platforms, which involve actors across multiple sides of the platform, and its influence on platforms companies’ political tactics. This paper aims to address how the multi-sided nature of digital platforms impacts the way they achieve policy change. This paper conducts a case study of how Chinese ride-hailing companies facilitated the enactment of a new, favourable national policy in 2016. Drawing on the literature of contentious politics, it finds that policy change can be achieved via rightful resistance, through which digital platforms leverage divisions within the multi-sided digital platform and within the government to push the frontiers of what is politically permitted. In the context of digital platforms, rightful resistance means (1) seeking support from powerful third parties, (2) using the rhetoric of the central policies, and (3) co-opting the incumbents.